The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5005/jp-journals-10024-1797
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dental Shade Guides and Experience on the Accuracy of Shade Matching

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 24 publications
1
32
1
Order By: Relevance
“…Some studies have indicated that shade selection improves with experience, while others did not find any differences between experienced dentists and those less experienced . Participants in this study had never taken the FM‐100 test, and had very little experience in shade selection except for their limited time shadowing or assisting in dental offices.…”
Section: Discussionmentioning
confidence: 70%
“…Some studies have indicated that shade selection improves with experience, while others did not find any differences between experienced dentists and those less experienced . Participants in this study had never taken the FM‐100 test, and had very little experience in shade selection except for their limited time shadowing or assisting in dental offices.…”
Section: Discussionmentioning
confidence: 70%
“…18 But various studies also report no influence of clinical experience in shade perception and selection. 14,[19][20][21] There are also studies which report the increase in shade matching ability of an individual after color education and training programs.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with the study by Musskopf et al 18 who concluded that patients and prosthodontists have different perceptions related to symmetry and esthetics around gingival margins of cemented crowns. 19 Moreover, patient's ability to detect symmetry cannot be relied when the evaluation is miniscule. Since this study used 3DMaster shade guide in both clinics and production laboratory, this could explain the good results in shade in this study, which is in agreement with Nakhaei et al, 19 who concluded that shade guide has an effect on shadematching results.…”
Section: Patient Dentist Evaluation Of the Quality Of Esthetic Of Cemmentioning
confidence: 99%
“…19 Moreover, patient's ability to detect symmetry cannot be relied when the evaluation is miniscule. Since this study used 3DMaster shade guide in both clinics and production laboratory, this could explain the good results in shade in this study, which is in agreement with Nakhaei et al, 19 who concluded that shade guide has an effect on shadematching results.…”
Section: Patient Dentist Evaluation Of the Quality Of Esthetic Of Cemmentioning
confidence: 99%